Group health education in general practice - Whitfield, Michael (1974)
Two simple experiments in group health education in a general practice are described. The first was with parents of young children in which an attempt was made to encourage self-sufficiency and a better use of the health services. The second was with a group of male bronchitics who were encouraged to alter their behaviour in an attempt to improve their health. Both experimental and control groups showed similar consulation rates after the educational sessions and there was little evidence of changed behaviour. I have found no evidence to encourage the use of such methods in general practice.